Punção aspirativa por agulha fina em lesão nodular da tireóide : estudo da precisão da análise citopatológica no Hospital Universitário Walter Cantídio - Beserra, Carlos Felipe Saraiva (1998)
Fine needle aspiration in thyroid disease: study on the accuracy of cytology at Hospital Universitário Walter Cantídio (HUWC-UFC). This study analised the accuracy of fine-needle aspiration technique (FNA) in patients referred to the Departamento de Cirurgia of the Universidade Federal do Ceará (UFC). These patients presented of thyroid nodular disease. The intention of the study was also to establish the routine use of the FNA in these patients. It was also part of the study to analyse risk factors to malignant thyroid disease and the importance of complementary exam in the patients studied. All patients had their clinical history taken and underwent physical examination, pré operative de routine exam and measurement of thyroid hormones. The aspirative form FNA was subjected to cytologic and histologic studies. Thyroid scan, ultrasonography and serological test to detect antithyroid antibodies were not performed in all patients. Endemiological risk factors such as age and sex were analised regarding their association with malignant thyroid disease. Sixty-six (66) patients were studied. They presented with clinically palpable thyroid lumps and were subjected to surgical treatment, which indications obeyed clinical and cytologic criteria. 63 patients were female and 3 male. Age average was 41,5 years, varying from 12 to 72 years. Risk factors were identified as patients with: 08 lumps with fast growth (12,1%), 9 lumps with hard texture at physical examination (13,6%). (08) Eight patients presented at physical examination palpable lymphnods (12,1%) and one (1) patient had hoarseness (1,5%). Results from cytologic were grouped as: benign – 30 (45,5), follicular neoplásica – 16 (24,2%), suspicious of being malignant – 5 (7,6%), malignant – 12 (18,2%), and inadequate – 3 (4,5%). Histology showed 22 malignant neoplasias and 44 benign nodules. Statistical analysis regarding sex, age, presence of hard lumps and palpable neck lymphnods homolateral to the lump showed an increased association with malignant disease (Fisher; p<0,05). However, there was no increase association with malignant age, patients who presented hoarseness, with lumps, with fast growth, and varied number to lumps and with different sizes. Combining cytology and histology enable to obtain the following indicators: sensitivity – 78,6% specificity – 94,5%, value of prediction – 90,5%, predictive positive value – 91,6%, false-positive – 8,4%, predictive negative value – 90,0%, and falsenegative – 10,0%. When included cytological results classified as indetermined (suspicious of malignancy and follicular neoplásica) as positive for malignant disease the indicators in the same sequence above were: 85%, 62,8%, 69,0%, 53,3%, 46,7%, 89,3% and 10,0%. Thyroid scan was performed in 23 patients and revealed 20 hypocaptent lumps (87%) – 6 of which were malignant (33,0%). No malignancy was found in two (2) normocaptent lumps and one (1) following results: 36 patients presented single lumps, 14 patients – multiple lumps and 2 patients had normal ultrasonography exam. There was a higher of malignancy in patients with single lumps turned to be malignant. When evaluating hormonal function there was a higher percentage of malignancy inpatients with normal hormonal disease (37,9%) – 22 out of 58 patients. When hypothyroidism was fund 25% this patients (1 out of 4) presented malignancy of nodular thyroid diseases and creditate the method as safe at the HUWC/UFC.